Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the quadratic equation [tex]\(x^2 + 12x - 11 = 0\)[/tex] by completing the square, follow these steps:
1. Start with the given equation:
[tex]\[ x^2 + 12x - 11 = 0 \][/tex]
2. Move the constant term to the right side of the equation:
[tex]\[ x^2 + 12x = 11 \][/tex]
3. Find the value that completes the square:
We need to add and subtract [tex]\(\left(\frac{b}{2}\right)^2\)[/tex] inside the equation, where [tex]\(b\)[/tex] is the coefficient of [tex]\(x\)[/tex]. In this case, [tex]\(b = 12\)[/tex].
[tex]\[ \left(\frac{12}{2}\right)^2 = 6^2 = 36 \][/tex]
4. Add and subtract this value on the left side of the equation:
[tex]\[ x^2 + 12x + 36 - 36 = 11 \][/tex]
[tex]\[ x^2 + 12x + 36 = 47 \][/tex]
5. Rewrite the left side as a perfect square trinomial:
[tex]\[ (x + 6)^2 = 47 \][/tex]
6. Take the square root of both sides:
[tex]\[ x + 6 = \pm\sqrt{47} \][/tex]
7. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = -6 \pm \sqrt{47} \][/tex]
8. Calculate the numerical values and round to three significant figures:
- The positive solution:
[tex]\[ x_1 = -6 + \sqrt{47} \approx 0.856 \][/tex]
- The negative solution:
[tex]\[ x_2 = -6 - \sqrt{47} \approx -12.856 \][/tex]
Therefore, the solutions to the equation [tex]\(x^2 + 12x - 11 = 0\)[/tex] are:
[tex]\[ x \approx 0.856 \quad \text{and} \quad x \approx -12.856 \][/tex]
rounded to three significant figures.
1. Start with the given equation:
[tex]\[ x^2 + 12x - 11 = 0 \][/tex]
2. Move the constant term to the right side of the equation:
[tex]\[ x^2 + 12x = 11 \][/tex]
3. Find the value that completes the square:
We need to add and subtract [tex]\(\left(\frac{b}{2}\right)^2\)[/tex] inside the equation, where [tex]\(b\)[/tex] is the coefficient of [tex]\(x\)[/tex]. In this case, [tex]\(b = 12\)[/tex].
[tex]\[ \left(\frac{12}{2}\right)^2 = 6^2 = 36 \][/tex]
4. Add and subtract this value on the left side of the equation:
[tex]\[ x^2 + 12x + 36 - 36 = 11 \][/tex]
[tex]\[ x^2 + 12x + 36 = 47 \][/tex]
5. Rewrite the left side as a perfect square trinomial:
[tex]\[ (x + 6)^2 = 47 \][/tex]
6. Take the square root of both sides:
[tex]\[ x + 6 = \pm\sqrt{47} \][/tex]
7. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = -6 \pm \sqrt{47} \][/tex]
8. Calculate the numerical values and round to three significant figures:
- The positive solution:
[tex]\[ x_1 = -6 + \sqrt{47} \approx 0.856 \][/tex]
- The negative solution:
[tex]\[ x_2 = -6 - \sqrt{47} \approx -12.856 \][/tex]
Therefore, the solutions to the equation [tex]\(x^2 + 12x - 11 = 0\)[/tex] are:
[tex]\[ x \approx 0.856 \quad \text{and} \quad x \approx -12.856 \][/tex]
rounded to three significant figures.
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.